1991
DOI: 10.1126/science.253.5017.309
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization Between European and Africanized Honey Bees in the Neotropical Yucatan Peninsula

Abstract: A population genetic analysis of honey bees of the Mexican neotropical Yucatan peninsula shows that the range expansion of Africanized bees there has involved extensive introgressive hybridization with European bees. Yucatan honey bee populations now include many colonies with intermediate morphologies. Genotypes of mitochondria have disassociated from historically correlated Africanized or European morphology, producing diverse phenotypic associations. This suggests that the size of resident European populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 23 publications
3
46
0
2
Order By: Relevance
“…Comparative studies of behaviour, population dynamics and morphometrics have revealed that these new bee populations are very similar to their African ancestors (summarized by Michener, 1975;Winston, 1992). Genetic polymorphism data have supported this conclusion, except in some regions where higher frequencies of European alleles can be detected (Lobo et al, 1989;Rinderer et al, 1991;Sheppard et al, 1991b). The latter phenomenon may be a result of prior high population densities or continued introduction of other honeybee races and/or ecological constraints for Africanized bees.…”
Section: Introductionmentioning
confidence: 53%
“…Comparative studies of behaviour, population dynamics and morphometrics have revealed that these new bee populations are very similar to their African ancestors (summarized by Michener, 1975;Winston, 1992). Genetic polymorphism data have supported this conclusion, except in some regions where higher frequencies of European alleles can be detected (Lobo et al, 1989;Rinderer et al, 1991;Sheppard et al, 1991b). The latter phenomenon may be a result of prior high population densities or continued introduction of other honeybee races and/or ecological constraints for Africanized bees.…”
Section: Introductionmentioning
confidence: 53%
“…The restriction fragments generated by the enzyme were electrophoresed in 1.1% agar gels in TBE buffer for 5 h at 5 V/cm, stained with ethidium bromide (0.01 mg/mL), and visualized under UV light. The Eco RI restriction patterns of mtDNA make it possible to discriminate subspecies of African or European origin (Smith and Brown, 1988;Hall and Muralidharan, 1989;Sheppard et al, 1991a, Rinderer et al, 1991. Since direct Eco RI digestion of mtDNA produced no clear pattern, the cytochrome B locus was amplified by PCR and the fragment obtained was digested with Bgl II.…”
Section: Methodsmentioning
confidence: 99%
“…In May 1998, we retraced the 10 transects through the Yucatan and Quintana Roo states of the Yucatan Peninsula chosen by Rinderer et al (1991) in 1989. Collections of adult worker bees and drones were made at four to 10 apiaries within each transect with approximately 10 colonies per apiary.…”
Section: Sampling Designmentioning
confidence: 99%
“…Prior to the arrival of Africanized bees in eastern Mexico, the northward-expanding population of Africanized bees had only encountered a tiny managed European population-they had been expanding into territory in which feralhoney bees were virtually absent (Roubik and Wolda 2001). Rinderer et al (1991) showed that hybridization was occurring between European and Africanized bees in the Yucatan in 1989, and the level of hybridization appears to have increased with time (Quezada-Euán 2000). However, the possibility remained that late-generation hybrids were at a selective disadvantage (Hall 1991) and that over time Africanized genotypes would replace European ones.…”
mentioning
confidence: 99%